Micromammals, taphonomy, paleoenvironments and human occupation during the Holocene in Arroyo Malo-3 (west-central Argentina) - Fernández, Fernando Julián (2015)
Micromammal remains from the archaeological sequence of Arroyo Malo-3 (AMA-3, 34º51’18’’S, 69º53’00’’W; soutwestern Mendoza, Argentina) are taxonomically identified, and taphonomic and paleoenvironmental conditions assessed. Small mammal remains (NISP = 7239, MNE= 7211, MNI = 730) were recovered from Holocene temporal units (Unit III = 8900-3810 years 14C BP; Unit II = 3810-2200 years 14C BP; Unit I = 2200-~100 years 14C BP). The taphonomic evidences such as pellets preserved in the stratigraphy, mostly moderate but also high digestive marks on teeth and postcraneal bones, and relative abundance patterns of skeletary parts, indicate that the main accumulating agents of the micromammal assemblages recovered from the units of AMA-3 would have been the Accipitriformes, possibly Geranoaetus melanoleucus (black-chested buzzard-eagle) or Buteo polyosoma (red-backed hawk). The scarce record of weathered bones, the absence of trampling marks, roots, sediment corrosion and water transport and the discovery of numerous specimens with manganese oxide impressions suggest that the remains had a rapid burial and good preservation, although with high moisture levels. The micromammal assemblages of AMA-3 showed a remarkable taxonomic stability, with some minor changes towards the Late Holocene. The major changes occurred in the recent micromammal assemblages close to the site, marked by an increase of shrubs attributable to human impact possibly produced by domestic livestock reinforced in the south of Mendoza since the 19th century. The paleoenvironmental and taphonomical information presented provides a relevant framework to improve archaeological studies of the biogeography and subsistence system of southern Mendoza hunter-gatherer populations during the Holocene.